ChemInform Abstract: Lanthanoid Template Isolation of the α‐1, 5 Isomer of Dicobalt(II)‐Substituted Keggin Type Phosphotungstates: Syntheses, Characterization, and Magnetic Properties. Issue 47 (3rd November 2016) - Gupta, Rakesh; Hussain, Firasat; Sadakane, Masahiro; Kato, Chisato; Inoue, Katsuya; Nishihara, Sadafumi
Abstract: The new compounds (IVa—j) are characterized by single crystal XRD, FT‐IR spectroscopy, electrospray ionization mass spectrometry, and magnetic measurements.